Election in Bangladesh: Challenges to Conduct Free and Fair Election - Baized, Md. Nazirul Hasan; Rahman, Ashiqur; Ferdous, Jannatul (Journal of Contemporary Local Politics, 2025)
This paper investigates the impediments to free and fair elections in Bangladesh, examines the effects of electoral violence and partisanship on democracy, and suggests reforms for clean and representative election processes. A descriptive qualitative design and content analysis are used in this study to find and explain typical patterns of electoral malpractices, intimidation of voters, political violence, and institutional bias in Bangladesh's elections.  The study finds that deep-seated political interference, electoral violence, and institutional flaws compromise electoral integrity in Bangladesh, particularly the absence of an independent Election Commission. These have diminished voter confidence, opposition boycotts, and democratic regression. To uphold electoral integrity in Bangladesh, the study recommends comprehensive political, legal, and institutional reforms. These include ensuring the independence of the Election Commission (EC), enforcing campaign finance laws, preventing pre-election violence, protecting media freedom, fostering inter-party consensus, and enhancing election monitoring mechanisms. In the future, studies on election governance in similar democracies, the prospects of electronic voting for fraud prevention, and the effect of reforms on democratic consolidation in Bangladesh are envisaged.